The Role And Significance Of Financial Resources In The Development Of Regions (Texas Journal of Multidisciplinary Studies, 2024)
Financial support for the competitive development of the country's economy is gaining importance today. The article discusses the need to adapt the financial system of our country to the priorities of ensuring integration with the countries of the world and to attract financial resources in order to increase the effectiveness of managing the country's financial potential and to solve problematic issues in the field of their attraction